Strengthening Religious Moderation in Interfaith Students At Dwijendra University, Denpasar - I Dewa Ayu Anom Tirtawati; I Wayan Winaja; I Gusti Ayu Suathi (UNHI PRESS, 2025)
Human harmony is being tested, divisive issues are rife, triggered by SARA elements and often viral, through social media news and mass media. Almost all lines have decreased in quality, especially in terms of empathy. The symbolic humanizing of humans is killed through the emergence of orientation worsening, humans who take refuge in spiritual words. As if what they state becomes absolute symbolic truth, and those who differ from their views are wrong. The wave of disruption makes a vibration of inner awareness, that humans must immediately clean up. One reflection is to create a sense of tolerance. Through a wide space of religious moderation, it will create religious harmony. Moderation is not only in the community environment, the family and school environment is also mandatory, from elementary school to college level must get a touch of strengthening religious moderation. The paradigm of strengthening religious moderation must be instilled in the minds of all citizens of the Republic of Indonesia. The above events triggered the author to examine religious moderation in interfaith students at Dwijendra University. Dwijendra University is one of the Universities that is synonymous with miniature of Indonesia, its students consist of various ethnicities, races, and religions, yet the students live in harmony side by side. This article presents answers to the questions of why the strengthening of religious moderation in interfaith students is carried out at Dwijendra University Denpasar, how is the process of strengthening religious moderation in interfaith students at Dwijendra University Denpasar, and what are the implications of strengthening religious moderation for interfaith students at Dwijendra University Denpasar? The theory used to analyze the answer to the problem formulation is Vygotsky's Constructivism theory, Albert Bandura's Social Learning theory, Jhon Waston's Behavior theory. The results of the analysis show that there are positive practices carried out as a strengthening of religious moderation in interfaith students at Dwijendra University. It is important to strengthen religious moderation, in the ability to understand differences between each other, behave and practice in religious harmony, in order to achieve Tri Hita Karana peace